Potent anti-inflammatory activity of the lectin-like domain of TNF in joints - Pinto, Ana Carolina Matias Dinelly; Nunes, Rodolfo de Melo; Nogueira, Igor Albuquerque; Fischer, Bernhard; Lucas, Rudolf; Girão-Carmona, Virgínia Claudia Carneiro; de Oliveira, Vivian Louise Soares; Amaral, Flavio Almeida; Schett, Georg; Rocha, Francisco Airton Castro (Frontiers in Immunology, 2022)
In view of the crucial role of tumor necrosis factor (TNF) in joint destruction, TNF inhibitors, including neutralizing anti-TNF antibodies and soluble TNF receptor constructs, are commonly used therapeutics for the treatment of arthropathies like rheumatoid arthritis (RA). However, not all patients achieve remission and moreover there is a risk for increased susceptibility to infection with these agents. Spatially distinct from its receptor binding sites, TNF harbors a lectin-like domain, which exerts unique functions that can be mimicked by the 17 residue solnatide peptide. This domain binds to specific oligosaccharides such as N’N’-diacetylchitobiose and directly target the α subunit of the epithelial sodium channel. Solnatide was shown to have anti-inflammatory actions in acute lung injury and glomerulonephritis models. In this study, we evaluated whether the lectin-like domain of TNF can mitigate the development of immune-mediated arthritis in mice. In an antigen-induced arthritis model, solnatide reduced cell influx and release of pro-inflammatory mediators into the joints, associated with reduction in edema and tissue damage as compared to controls indicating that TNF has anti-inflammatory effects in an acute model of joint inflammation via its lectin-like domain.